ANALYSIS OF STUDENTS' MATHEMATICAL CRITICAL THINKING SKILLS ON STATISTICS MATERIAL IN MIDDLE SCHOOL - Dahlia, Dahlia; Panjaitan, Dedy Juliandri (JURNAL EDUSCIENCE, 2024)
The purpose of the research conducted by the author was to describe the analysis of students' mathematical critical thinking skills conducted in class VIII-1 on statistics material. The type of research used in this research is qualitative research with a descriptive approach. In this study, data was collected by giving written tests of critical thinking skills and interviews. The results of this study were that subjects in the high category were able to correctly fulfill all indicators of mathematical critical thinking ability, subjects in the medium category were able to carry out 3 indicators of mathematical critical thinking ability, and subjects in the low category were only able to carry out 1 indicator. Based on the results of the analysis of data processing, the data processing of the results of student answers shows that the average acquisition of written test questions is 51.38%. The conclusion is that the mathematical critical thinking skills of class VIII-1 students of SMP Negeri 22 Medan are classified as low. Therefore, the mathematical critical thinking skills of class VIII-1 students of SMP Negeri 22 Medan still need further training so that they can be improved.Keywords: Critical Thinking Ability; StatisticsAbstrak Tujuan penelitian yang dilakukan penulis adalah untuk mendeskripsikan analisis kemampuan berpikir kritis matematis siswa yang dilakukan di kelas VIII-1 pada materi statistika. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif dengan pendekatan deskriptif. Dalam penelitian ini data dikumpulkan melalui pemberian tes tertulis kemampuan berpikir kritis dan wawancara.  Hasil penelitian ini adalah Subjek dalam kategori tinggi mampu memenuhi semua indikator kemampuan berpikir kritis matematis dengan benar, subjek dalam kategori sedang mampu melaksanakan 3 indikator kemampuan bepikir kritis matematis, dan subjek dalam kategori rendah hanya mampu melaksanakan 1 indikator saja. Berdasarkan hasil analisis pengolahan data, pengolahan data hasil jawaban siswa menunjukkan rata-rata perolehan hasil soal tes tertulis adalah 51,38%. Kesimpulannya adalah kemampuan berpikir kritis matematis siswa kelas VIII-1 SMP Negeri 22 Medan tergolong rendah. Oleh karena itu, kemampuan berpikir kritis matematis siswa kelas VIII-1 SMP Negeri 22 Medan masih perlu dilatih lebih lanjut agar dapat ditingkatkan.Kata Kunci: Kemampuan Berpikir Kritis; Statistika